Lactobacillus rhamnosus GG protects the intestinal epithelium from radiation injury through release of lipoteichoic acid, macrophage activation and the migration of mesenchymal stem cells. Issue 6 (22nd June 2018) - Riehl, Terrence E; Alvarado, David; Ee, Xueping; Zuckerman, Aaron; Foster, Lynn; Kapoor, Vaishali; Thotala, Dinesh; Ciorba, Matthew A; Stenson, William F
Abstract : Objective: Lactobacillus rhamnosus GG (LGG), a probiotic, given by gavage is radioprotective of the mouse intestine. LGG-induced radioprotection is toll-like receptor 2 (TLR2) and cyclooxygenase-2 (COX-2)-dependent and is associated with the migration of COX-2+mesenchymal stem cells (MSCs) from the lamina propria of the villus to the lamina propria near the crypt epithelial stem cells. Our goals were to define the mechanism of LGG radioprotection including identification of the TLR2 agonist, and the mechanism of the MSC migration and to determine the safety and efficacy of this approach in models relevant to clinical radiation therapy. Design: Intestinal radioprotection was modelled in vitro with cell lines and enteroids as well as in vivo by assaying clinical outcomes and crypt survival. Fractionated abdominal and single dose radiation were used along with syngeneic CT26 colon tumour grafts to assess tumour radioprotection. Results: LGG with a mutation in the processing of lipoteichoic acid (LTA), a TLR2 agonist, was not radioprotective, while LTA agonist and native LGG were. An agonist of CXCR4 blocked LGG-induced MSC migration and LGG-induced radioprotection. LGG given by gavage induced expression of CXCL12, a CXCR4 agonist, in pericryptal macrophages and depletion of macrophages by clodronate liposomes blocked LGG-induced MSC migration and radioprotection. LTA effectively protected the normal intestinal crypt, but not tumours in fractionated radiation regimens. Conclusions: LGG acts as a 'time-release capsule' releasing radioprotective LTA. LTA then primes the epithelial stem cell niche to protect epithelial stem cells by triggering a multicellular, adaptive immune signalling cascade involving macrophages and PGE2 secreting MSCs. Trial registration number: NCT01790035 ; Pre-results.